The attractor method - A technique to quantify differences of cyclic processes and their variability - Vieten, M. M.; Jensen, R. L. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study is to introduce a new, very sensitive method to quantify differences of movement pattern and the variability of cyclic processes. While the method is applicable to practically all cyclic processes, we restrict ourselves to an example of walking under various conditions